Интерференционный переключатель резонансного СВЧ-компрессора: полезная модель - Артеменко С. Н. Сергей Николаевич; Августинович В. А. Владимир Андреевич; Каминский В. Л. Валерий Людвигович; Новиков С. А. Сергей Автономович; Юшков Ю. Г. Юрий Георгиевич
опубл. 10.09.11